Consumer Satisfaction in E-shopping: A Factor Analysis of Customer Satisfaction in Malaysia - Nurshahrizleen Ramlan, Sayang; Maizura Abd Rashid, Intan; Hanie Abu Samah, Irza (International Journal of Psychosocial Rehabilitation, 2020)
This study is taking place to analyze the factors that might affect the customer’s online purchasing dissatisfaction using e-shopping. When the customers are unsatisfied with a selective online shop, they will not repeat purchasing there or might as well ban the shop. Customer satisfaction is the consequence of customer experience through different stages of purchase, as the customers cannot physically contact the products when they buy the products, and they are only based on the information provided by the sellers. Generally, the benefit of online purchasing merely depends on the customer's satisfaction during their time to purchase the product or service. The importance of this study is to focus on the awareness, satisfaction level, and problems that had been faced by customers, especially teenagers, on online purchasing. Hence, the result of this research might be useful for customers who always do online purchasing. Lastly, lack of product information and fraud and security were found to have a significant effect on factors affecting customers’ online purchasing dissatisfaction with a significance level of (sig. t = 0.005) with a positive beta.